Sprzeciw małżonka dłużnika wobec zamierzonej przez dłużnika spłaty długu środkami z majątku wspólnego małżonków - Lutkiewicz-Rucińska, Anita (PRAWO i WIĘŹ, 2025)
A creditor whose debtor is one of the spouses may demand satisfaction from the entire joint property of the spouses (Article 41 § 1 of the Family and Guardianship Code) or from certain components of that property (Article 41 § 2 and 3 of the Family and Guardianship Code). However, in Article 361 of the Family and Guardianship Code, the legislator provided for the institution of a spouse’s objection to the other spouse’s intended management activity of joint property of the spouses. In view of the above regulations, the paper discusses the issue of the admissibility of a spouse’s objection in a case where the spouse who is a debtor intends to repay the debt owed by him or her with funds from the joint property of the spouses, the effectiveness of the objection against the creditor, the legal consequences of the objection raised, and the impact of the institution of objection on the situation of the creditor of one of the spouses. In the author’s opinion, in order to determine whether the objection of a spouse against the debtor’s intention to repay the debt from the joint property of the spouses is admissible, not only the content of Article 361 § 1 and Article 41 of the Family and Guardianship Code is relevant, but also the limitation period for claims against the debtor spouse. This paper also expresses the view that although the institution of objection serves a protective function towards the debtor’s spouse, due to the content of Article 361 § 2 of the Family and Guardianship Code, which regulates the effectiveness of an objection against a third party, it poses a threat to the legitimate interests of the creditor.